OP0206 Interactions Between Smoking and Methylation Status is Highly Predictive of Radiographic Progression in Ankylosing Spondylitis. (9th June 2015) - O'Rielly, D.D.; Haroon, N.; Gao, Z.; Zhang, Y.; Codner, D.; Zhai, G.; Dohey, A.; Zhou, A.; Al Ghanim, N.; Hamilton, S.; Inman, R.D.; Rahman, P.
Abstract : Background: The variability in the rate of radiographic progression in ankylosing spondylitis (AS) and the role of smoking, as an independent risk factor for radiographic progression, has been well documented. We have recently identified multiple epigenetic variants associated with ankylosis in AS using a genome-wide epigenetic approach. In this study, we examined the recently identified epigenetic markers in an independent AS cohort to assess radiographic progression and determine if an interaction exists with smoking status. Methods: Our replication cohort consisted of 76 AS patients (16 females; 32 smokers; 56 HLA-B27 +) that had serial radiographs on average 3 years apart (range 1.2 to 7.5 yrs). Of the 76 patients, 35 patients exhibited radiographic progression (change in mSASSS score >0). The mean radiographic progression for the entire group was 0.99 mSASSS/yr. The DNA methylation experiments on 17 CpG sites were designed using EpiTyper and performed on a Sequenom MassArray 4 system. The association between methylation score and radiographic progression rate was examined by multiple linear regressions after controlling for age of onset and gender. An interaction between methylation score and smoking status was introduced into the model to examine the association in the smokers and non-smokers, respectively. The Akaike information criterion (AIC) was used to assess the goodness of fit. Methylation sites with more than 15% of data missing were excluded from the analysis. The total methylation score of 7 CpG sites had the best goodness of fit. Results: In the univariate analysis, high total methylation score was significantly associated with less radiographic progression (β=-0.97; 95%CI=-1.91:-0.02; p=0.04). Smokers demonstrated worse radiographic progression than non-smokers, but it was not statistically significant (p=0.62). In the multivariate analysis, the interaction between methylation score and smoke status was statistically significant (p=0.008). Among smokers, high total methylation score was significantly associated with less radiographic progression (β=-2.01; 95%CI=-3.26:-0.75; p=0.0017). No such association was observed among non-smokers. Conclusions: This is the first study to demonstrate how epigenetic factors can influence radiographic progression in AS. Specifically, the results from this study reveal a significant association between smoking, methylation status and radiographic progression in AS. Disclosure of Interest: None declared